Dirâsah Taqâbuliyyah Baina Al-Lughah Al-‘Arabiyyah Wa Allughah Al-Indûnîsiyyah ‘Alâ Mustawâ Maful Fih Wa Alistifâdah Minhâ Fî Ta‘Lîm Al-Lughah Al-‘Arabiyyah Li Almubtadi’în Al-Indûnisiyyî - Muslihin; Hisan Mursalin (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2021)
هدفت هذه الدراسة إلى دراسة المفعول فيه في اللغة العربية واللغة الإندونيسية لاكتشاف أوجه التشابه والاختلاف بينهما من ثلاثة جوانب: نحوي وصرفي ودلالي، ثم تصميم وحدة تعليمية لغوية لتعليم اللغة العربية للمبتدئين الإندونيسيين على مستوى المفعول فيه بناء على نتائج هذه الدراسة التقابلية. وقد استخدمت هذه الدراسة المنهج الوصفي التحليلي للبحث عن خصائص المفعول فيه في اللغتين العربية والإندونيسية، ثم استخدمت منهج التحليل التقابلي لمقارنة نظام المفعول فيه بين اللغتين العربية والإندونيسية ثم استخراج أوجه التشابه والاختلاف من هذه المقارنة. وتواصلت هذه الدراسة إلى نتيجتين: أولاهما: وجود التشابه والاختلاف بين اللغة العربية واللغة الإندونيسية على مستوى المفعول فيه في ثلاثة جوانب وهي جانب نحوي وصرفي ودلالي، وثانيهما أنه يمكن الاستفادة من نتائج هذه الدراسة في تصميم وحدة تعليمية لغوية لتعليم اللغة العربية للمبتدئين الإندونيسيين على مستوى المفعول فيه. This study aimed to study the comparison of adverb of place and time between Arabic and Indonesian language to find out the similarities and differences in terms of morphology, syntax, and semantic, and then to prepare of adverb of place and time the design to teach the Arabic language at the level of the comparison of for the Indonesian beginners based on the results of this contrastive study. This study used descriptive analytical methodology to identify the characteristics of adverb of place and time in Arabic and Indonesian language, and used method of comparative analysis to compare the Arabic and Indonesian language at the level of adverb of place and time and to deriving of their similarities and differences. The results of this study are: the first is there are similarities and differences of the comparison of adverb of place and time in Arabic and Indonesian in terms of morphology, syntax, and semantic, and the second is the results of this study can be used in preparing the design teaching the Arabic language at the level of the comparison of adverb of place and time for the indonesian beginners.